La secrecion de nectar de la campanilla morada (Ipomoea triloba). Tres años de observaciones - Perez Piñeiro, A.=700 1 Carralero, R.; Garcia, O.
(Es, En)
Ilus., 9 ref.
Keywords: IPOMOEA; NECTAR; SECRECIONES DE LAS PLANTAS; FLORACION; CUBA